2015
DOI: 10.15407/hftp06.04.474
|View full text |Cite
|
Sign up to set email alerts
|

Determination of molybdenum oxidation state on the mechanochemically treated MoO3

Abstract: The molybdenum oxidation degree in the MoO 3 samples after mechanochemical treatment in various media (air, water, ethanol)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…The as-deposited film and the one annealed at 300 • C exhibited only a large peak at around 1.7 Å, corresponding to the nearest oxygen neighbors (Mo-O) without additional shells. This is in agreement with previous XANES spectra of these same samples that pointed out the presence of disordered phases [23]. On the other hand, a structural ordering of the coating was observed at higher annealing temperatures (> 350 • C).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The as-deposited film and the one annealed at 300 • C exhibited only a large peak at around 1.7 Å, corresponding to the nearest oxygen neighbors (Mo-O) without additional shells. This is in agreement with previous XANES spectra of these same samples that pointed out the presence of disordered phases [23]. On the other hand, a structural ordering of the coating was observed at higher annealing temperatures (> 350 • C).…”
Section: Resultssupporting
confidence: 93%
“…The latter has a well-defined pre-edge peak at 20,005.6 eV (peak A), with two other major components at 20,025.7 eV and 20,037.2 eV (peaks B and C). The broadened features of the as-deposited film, in comparison with the reference spectra of the α-MoO 3 spectrum, confirmed that this film was mainly disordered [23][24][25]. Within the initial annealing stage at 300 • C, the ordering process (flagged by peak C) started to appear, although the film remained disordered.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…The broadening of the peaks suggests that they consist of several overlapping signals, which is in line with previously reported studies. 28,30,31,34,35 The lower values of the absorption g-tensor scalar around 2.003, which were detected in reduced samples (H 2 , vacuum, N 2 ), can be ascribed to single ionized oxygen vacancies O • ‾ (radical oxygen), 35 see Fig. 3b.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 97%
“…Molybdenum exhibits oxidation states ranging from +2 to +6 [ 1 2 ], leading to a range of molybdenum oxides. Molybdenum oxides include the fully stoichiometric MoO 3 with a large bandgap above 2.7 eV, the reduced oxides MoO 3− x with oxygen vacancies, and the semimetal MoO 2 .…”
Section: Introductionmentioning
confidence: 99%